2000
DOI: 10.1097/00007890-200002150-00020
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Gradual Onset Brain Death for Transplant-Associated Studies in Rats1

Abstract: We describe a controlled model of gradual onset brain death in the rat in which normotension can be sustained for several hours before the kidneys are removed for transplantation. Despite stable donor blood pressure, ischemia of peripheral organs may explain in part the increased incidence of delayed graft function of cadaver kidneys compared with those from living donors. This model is suitable for transplant-related studies involving organs from donors with irreversible central injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 10 publications
2
46
0
Order By: Relevance
“…For raising the intracranial pressure gradually, the balloon was inflated with 40 l/min saline until respiration ceased. Using this protocol, previous studies demonstrated brain death by electroencephalogram and magnetic resonance imaging (10). The absence of reflexes, apnea, and maximally dilated and fixed pupils confirmed the condition.…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…For raising the intracranial pressure gradually, the balloon was inflated with 40 l/min saline until respiration ceased. Using this protocol, previous studies demonstrated brain death by electroencephalogram and magnetic resonance imaging (10). The absence of reflexes, apnea, and maximally dilated and fixed pupils confirmed the condition.…”
Section: Methodsmentioning
confidence: 65%
“…Brain death induction. Brain death was produced by balloon inflation of a Fogarty catheter introduced into the subdural space through an occipital burr hole as previously described (10). Briefly, anesthesia was induced with diethyl ether in all animals and maintained by intraperitoneal administration of pentobarbital (30 mg/kg Nembutal Sodium Solution; Abbott Laboratories, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A continuous and prolonged expansion of a supratentorial balloon catheter or intracranial haemorrhage leads to cerebrospinal ischaemia, starting in the cerebrum with a progression to the mesencephalon, pons, medulla oblongata and spinal cord in a rostro-to-caudal fashion (Schrader et al 1985a). Depending on the anatomical structures involved in central ischaemia, haemodynamic changes occur due to the activation or inhibition of the autonomic nervous system (Pratschke et al 2000). In our study, macroscopic evaluation of the position of the balloon catheter showed that it was located between the skull, the tentorium and the occipital lobe.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that living donor organs show a better outcome than organs from cadaveric donors (1) cannot be fully attributed to shorter cold ischemia time and better immunological conditions, thus indicating that BD can cause relevant pathopysiological changes. This central catastrophe (2) appears to be a primary injury proceeding the secondary effects of ischemia/reperfusion (3). A combination of these effects leads to enhanced immunogenicity, which, after engraftment, can accelerate the recipient's immune response (4).…”
Section: Introductionmentioning
confidence: 99%